2017
DOI: 10.1167/iovs.16-19767
|View full text |Cite
|
Sign up to set email alerts
|

Gsg1, Trnp1, and Tmem215 Mark Subpopulations of Bipolar Interneurons in the Mouse Retina

Abstract: PurposeHow retinal bipolar cell interneurons are specified and assigned to specialized subtypes is only partially understood. In part, this is due to a lack of early pan- and subtype-specific bipolar cell markers. To discover these factors, we identified genes that were upregulated in Blimp1 (Prdm1) mutant retinas, which exhibit precocious bipolar cell development.MethodsPostnatal day (P)2 retinas from Blimp1 conditional knock-out (CKO) mice and controls were processed for RNA sequencing. Genes that increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…We used the core vertebrata matrix and set the relative profile score threshold to 90% ( S2 Table ). Using previously generated RNA-seq data from the P2 retina [ 29 ], we excluded those genes that showed no expression in the retina. JASPAR predicted the Otx2 binding site and the sequence upstream matched an ROR response element (AGGTCA with 5bp of A/T rich upstream sequence) [ 45 ] ( Fig 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the core vertebrata matrix and set the relative profile score threshold to 90% ( S2 Table ). Using previously generated RNA-seq data from the P2 retina [ 29 ], we excluded those genes that showed no expression in the retina. JASPAR predicted the Otx2 binding site and the sequence upstream matched an ROR response element (AGGTCA with 5bp of A/T rich upstream sequence) [ 45 ] ( Fig 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…JASPAR predicted the Otx2 binding site and the sequence upstream matched an ROR response element (AGGTCA with 5bp of A/T rich upstream sequence) [ 45 ] ( Fig 6C ). All three ROR genes ( Rora , Rorb , and Rorc ) are made in the P2 retina, but Rorb is expressed at the highest levels [ 29 ]. Thus, we attempted ChIP with multiple RORβ antibodies, but none of them gave reproducible results (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISH revealed that col23a1 mRNA was distributed in the central-most region of INL, in a region between syt1+ and gad1+ amacrine cells and synaptotagmin 2 (Syt2)-expressing OFF-bipolar cells (Fox and Sanes, 2007 ; Figure 3C ). While additional studies are needed to determine the exact cellular origin of col23a1 in the retina, these results suggest it may be generated by ON-bipolar cells, a population of neurons that lie between inhibitory amacrine cells and OFF-bipolar cells (Figure 3C ; Park et al, 2017 ).…”
Section: Resultsmentioning
confidence: 98%
“…Currently little is known about the transmembrane protein 215 (XM_014194795) and its function. It is conserved among vertebrate species and is expressed in mouse bipolar cells (Park et al, 2017). An attractive speculation is, because of the increase of its transcription in old cells, that it is involved in the age-dependent removal of cells from circulation.…”
Section: Discussionmentioning
confidence: 99%